2011
DOI: 10.1039/c1ob05877k
|View full text |Cite
|
Sign up to set email alerts
|

Peptide dendrimer enzyme models for ester hydrolysis and aldolization prepared by convergent thioether ligation

Abstract: Peptide dendrimers with multiple histidines or N-terminal prolines efficiently catalyze ester hydrolysis or aldol reactions in aqueous medium. Part of the catalytic proficiency of these dendritic enzyme models stems from multivalency effects observed in G2, G3 and G4 dendrimers displaying multiple catalytic groups in their branches. To study multivalency in higher generation systems, G4, G5 and G6 peptide dendrimers were prepared by a convergent assembly. Thus, peptide dendrimers bearing four or eight chloroac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 58 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…This is probably a result of the steric crowding in the G3 dendrimer with some of the amino termini not exposed to the coupling reagents. 18 The isolated yields of these various chloroacetylated core dendrimers after SPPS and HPLC purification were above 25% for G1 and G2, but only 3-5% for G3 cores, reflecting the generally more difficult synthesis of G3 peptide dendrimers ( Table 1). We therefore turned our attention to a convergent approach using our recently reported multivalent ClAc ligation method as an efficient strategy to access G3 and G4 peptide dendrimers (Fig.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably a result of the steric crowding in the G3 dendrimer with some of the amino termini not exposed to the coupling reagents. 18 The isolated yields of these various chloroacetylated core dendrimers after SPPS and HPLC purification were above 25% for G1 and G2, but only 3-5% for G3 cores, reflecting the generally more difficult synthesis of G3 peptide dendrimers ( Table 1). We therefore turned our attention to a convergent approach using our recently reported multivalent ClAc ligation method as an efficient strategy to access G3 and G4 peptide dendrimers (Fig.…”
Section: Synthesismentioning
confidence: 99%
“…17 Considering that many of the reported high affinity multivalent glycosidic ligands for lectins feature an 8-fold or higher multivalency, we asked the question whether the binding affinity and biological activity of dendrimers GalAG2 and GalBG2 might be increased in higher valency analogs as observed in other series of tight binding LecA ligands. 18 Hemagglutination inhibition, isothermal titration calorimetry and biofilm inhibition assays are reported that show that G3 dendrimers bind LecA slightly better than their parent G2 dendrimers and induce complete biofilm inhibition and dispersal of P. aeruginosa biofilms, while G4 dendrimers have reduced binding and no biofilm inhibition. 18 Hemagglutination inhibition, isothermal titration calorimetry and biofilm inhibition assays are reported that show that G3 dendrimers bind LecA slightly better than their parent G2 dendrimers and induce complete biofilm inhibition and dispersal of P. aeruginosa biofilms, while G4 dendrimers have reduced binding and no biofilm inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…25 Initial studies with enzyme models highlighted multivalency effects of histidine in esterase dendrimers, [26][27][28] and of N-terminal proline in aldolase dendrimers. 29 …”
mentioning
confidence: 99%
“…We used 2DP-space to analyze a family of bridged bicyclic peptides resulting from a double chloroacetyl thioether (ClAc) ligation 62 of a first generation peptide dendrimer containing two cysteine residues in its stem. The two possible isomers formed by cyclization were accessible by SPPS either as mixture, or as single isomers using an orthogonal protecting group strategy ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%